LEARNING DYNAMICS OF SOCIOLOGY IN SENIOR HIGH SCHOOL THROUGH JIGSAW COOPERATIVE LEARNING - Angela Sastri (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2021)
The aim of this research is 1. To find out how the application of Jigsaw type cooperation learning models in Sociology subject in Senior High School. 2 To find out how the Jigsaw Cooperation Learning Models in improving students learning outcomes. The method used in this analysis is a journal review. Data sources are obtained from several journals regarding jigsaw type cooperative learning models by reviewing jigsaw. Journal review is making analysis and making a critical and in-depth synthesis of these journals. Based on the results of the analysis it can be concluded that the application of the learning model by forming an origin group and an expert group can have a positive influence on increased learning outcomes. Jigsaw type cooperative learning models in improving student learning outcomes can be pursued through improving students’ reasoning abilities as well as increasing students learning activities by helping students to be more active in learning and take responsibility for the material being studied and improve communication skills.